PRONUNCIATION OF DIPHTHONGS BY SEVENTH GRADE STUDENTS - Ni Luh Desy Suari Dewi (LPPM Universitas Dhyana Pura, 2018)
ABSTRACTThe differences between the English and Indonesian phonemes especiallyin vowels sounds can cause Indonesian students face difficulties in pronuncing wordsin English containing certain vowels. So, it will be important for the Indonesianstudents to learn about English vowels sound.Therefore, a research by using qualitative method was arranged in order toknow the production of diphthongs sounds by the students. This research wasconducted in a private class which consists of 10 students. The students are seventthgrade students of Junior High School.Based on the analysis of the production of diphthongs, it can be seen thatdiphthongs [eɪ], [aɪ], [ↄɪ] can be produced correctly by those ten students. Meanwhile,diphthongs [əʊ], [aʊ], [eə], [ɪə], [ʊə], [ↄə] can not be produced perfectly by the students.Those diphthongs were produced like simple sounds or monophthongs. It means thatthe students found difficulties in producing some English diphthongs.Key words: English vowels, simple vowels, diphtongsABSTRAKPerbedaan fonem bahasa Inggris dan bahasa Indonesia terutama padabunyi vokal dapat menyebabkan pembelajar berbahasa Indonesia kesulitan dalammengucapkan kata-kata yang mengandung beberapa bunyi vokal bahasa Inggris,terutama pada bagian diphthongs. Jadi, sangatlah penting bagi pembelajar untukmempelajari bunyi vokal berbahasa Inggris.Oleh sebab itu, sebuah penelitian dilakukan dengan metode kualitatif untukmengetahui pengucapan bunyi diphthongs oleh siswa yang sedang belajar bahasaInggris. Penelitian ini dilaksanakan pada sepuluh orang siswa kelas tujuh yangmengikuti bimbingan belajar bahasa Inggris.Dari penelitian ini, dapat disimpulkan bahwa bunyi diphthongs [eɪ], [aɪ],[ↄɪ] bisa diucapkan dengan baik oleh siswa. Namun, diphthongs [əʊ], [aʊ], [eə], [ɪə],[ʊə], [ↄə] tidak bisa diucapkan dengan sempurna oleh siswa. Diphthongs tersebutdiucapkan seperti bunyi vokal sederhana (monophthongs). Hal ini menunjukkanbahwa, siswa menemukan kesulitan dalam pengucapan bunyi diphthongs.Kata Kunci: Bunyi vokal bahasa Inggris, bunyi vokal sederhana, diphthongs